Encapsulation of enzyme in large mesoporous material with small mesoporous windows - Malvi, Bharmana; Sen Gupta, Sayam (Chemical Communications, 2012)
Trypsin has been encapsulated in the mesopores of a hierarchical mesoporous silica material synthesized via Cu(I) catalyzed azide-alkyne click reaction between azide functionalized large spherical SBA-15 particles and alkyne functionalized mesoporous silica nanoparticles (MSNs). Encapsulated trypsin functions as an efficient biocatalyst and can be recycled several times.